Multi-scenario assessment of landscape ecological risk in the transitional zone between the warm temperate zone and the northern subtropical zone - Li, Chenghang; Qin, Fen; Liu, Zhenzhen; Pan, Ziwu; Gao, Dongkai; Han, Zhansheng (Frontiers in Ecology and Evolution, 2024)
Climate transition zones are ecologically sensitive regions that respond to changes in complex natural conditions. Analyzing the spatiotemporal evolution trends and impact factors of landscape ecological risk is crucial for maintaining regional ecosystem security. However, research predominantly focused on the past analytical paradigm, which often needed more strategic predictions for future scenarios tailored to diverse developmental requirements. This study analyzed land use changes in the Huai River Basin during 2000, 2010, and 2020 and used the Future Land Use Simulation model to conduct a multi-scenario simulation for 2030. Subsequently, this study assessed the landscape ecological risk from 2000 to 2030 and analyzed the influencing mechanisms using the ridge regression model. The results showed that: (1) The primary transitions were concentrated between cropland and construction land. By 2030, the area of construction land was projected to continue to expand, with the greatest increase of 2906 km2 anticipated in the natural development scenario. (2) The overall spatial pattern of landscape ecological risk showed a “high in the east and low in the west” distribution, with the lowest risk areas predominating (accounting for over 43%). Over the past 20 years, the risk initially increased and then decreased, and by 2030, the risk was expected to decline further. (3) The risk exhibited significant positive spatial autocorrelation. By 2030, the constraint of spatial location on risk distribution would decrease. Local spatial clustering was mainly characterized by “Low-Low” regions (accounting for 20%). (4) Vegetation cover consistently correlated negatively with ecological risk and was the most influential factor, with relative contribution rates all exceeding 21%. The findings have provided a scientific reference for the ecological and environmental management of areas with intense human activity under complex climatic conditions.